Analisis Struktural Cerpen “Kuli Kontrak” Karya Mochtar Lubis - Rahma Dela; Abdurahman . (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
The short story Kuli Kontrak by Mochtar Lubis reflects social realities during the colonial era, particularly the suffering and exploitation of contract laborers. This study aims to describe the intrinsic structure of the short story, including theme, plot, characters, setting, point of view, and moral message. The research employs a qualitative descriptive method using a structural approach. Data were collected through literature review and textual analysis. The findings reveal that the story highlights social injustice against laborers through a progressive plot and realistic characterization. The third-person omniscient point of view strengthens the delivery of moral values concerning humanity and justice. This short story holds significant social value and is relevant for literary studies and character education.